Síndrome de Klinefelter con deficiencia parcial de hormona de crecimiento. - TORI TORI, Carlos; ROE B., Carlos (Revista Médica Herediana, 2015)
We present a case of Klinefelter’s syndrome and short stature due to partial growth hormone deficiency. His height was below the third percentile for age and his bone age lagged behind four years. Cases like this are generally due to the presence of a an isochromosome Xq or to an isolated partial or total deficiency of growth hormone, or to partial or panhypopituitarism. We wish de emphasize the rare association between Klinefelter syndrome and growth hormone deficiency.